Evidence-Based Recommendations for Improving National Environmental Policy Act Implementation - Ruple, John C.; Pleune , Jamie; Heiny, Erik (Columbia Journal of Environmental Law, 2022)
The National Environmental Policy Act requires federal agencies to consider environmental impacts before acting. NEPA is the Magna Carta of U.S. environmental law, a topic of intense debate, and the subject of ongoing rulemaking efforts. Prior NEPA scholarship focuses almost exclusively on Environmental Impact Statements, which account for just 1% of all NEPA decisions. Little is known about the length of time required to complete the other 99% of agency decisions, which involve a more streamlined review. This is a critical gap in the literature because NEPA compliance involves an estimated 50,000 federal decisions annually. NEPA reform, we believe, should begin with a careful understanding of NEPA practice at all levels of review. To help advance effective NEPA reform, we studied over 41,000 NEPA decisions completed by the U.S. Forest Service between 2004 and 2020. Using this data, we conducted a multivariate statistical analysis of the length of time required to complete the NEPA process at each level of review. We then investigated factors associated with longer decisionmaking times. Our model accounts for interactions between 3 levels of NEPA analysis, 43 activities involved in these decisions, 9 geographic regions, and the year of project initiation. Contrary to widely held assumptions, we found that a less rigorous level of analysis often fails to deliver faster decisions. Delays, we found, are often caused by factors only tangentially related to the Act, like inadequate agency budgets, staff turnover, delays receiving information from permit applicants, and compliance with other laws. Improving NEPA efficacy, we argue, should therefore focus on improving agency capacity. This approach, we believe, would improve the NEPA process and advance NEPA’s mandate to engage with key stakeholders and carefully consider environmental impacts before making decisions.